Bridging the Gap: Architecture and Structural Engineering - A., Faridah; A., Abdullah Sani; R., Ismail (2004)
Division of the responsibility for the design and construction of the built environment between architecture and engineering is a relatively modern development. Up until about 150 years ago, a single individual, the ‘Master builder’ performed the roles of Engineer and Architect for the design of a building or bridge. Today, Structural Engineers and Architects are educated completely independently. Although both play a major part in designing and building a nation's infrastructure, they are not encouraged to fully understand the work of each other. There is a dire need to Bridge the Gap between Engineers and Architects. This paper focuses on doing that at the tertiary education level. It does not propose a carefully formulated curriculum but endeavours to provoke creative thinking in the teaching of the two salient fields of the built environment.